2022
DOI: 10.1371/journal.pntd.0010358
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing one-dose and two-dose cholera vaccine allocation in outbreak settings: A modeling study

Abstract: Background A global stockpile of oral cholera vaccine (OCV) was established in 2013 for use in outbreak response and are licensed as two-dose regimens. Vaccine availability, however, remains limited. Previous studies have found that a single dose of OCV may provide substantial protection against cholera. Methods Using a mathematical model with two age groups paired with optimization algorithms, we determine the optimal vaccination strategy with one and two doses of vaccine to minimize cumulative overall infe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 53 publications
2
13
0
Order By: Relevance
“…Considering that as of the summer of 2022, the United States had secured 1.1 million of MVA vaccines and that there are an estimated 1.7 million people at high risk ( 11 ), our results suggest that dose-sparing strategies would outperform full-dose vaccination provided that the fractional dose retains at least 60% effectiveness of the full dose. These results are consistent with previous studies for other infectious diseases, such as cholera ( 12 , 13 ), influenza ( 14 , 15 ), and COVID-19 ( 16 ), which have found that dose-sparing strategies are optimal when the fractional-dose VE is around half as effective as the full dosage. The fewer the doses of MVA vaccine available, the projected payoff from using dose-sparing strategies increases.…”
Section: Discussionsupporting
confidence: 92%
“…Considering that as of the summer of 2022, the United States had secured 1.1 million of MVA vaccines and that there are an estimated 1.7 million people at high risk ( 11 ), our results suggest that dose-sparing strategies would outperform full-dose vaccination provided that the fractional dose retains at least 60% effectiveness of the full dose. These results are consistent with previous studies for other infectious diseases, such as cholera ( 12 , 13 ), influenza ( 14 , 15 ), and COVID-19 ( 16 ), which have found that dose-sparing strategies are optimal when the fractional-dose VE is around half as effective as the full dosage. The fewer the doses of MVA vaccine available, the projected payoff from using dose-sparing strategies increases.…”
Section: Discussionsupporting
confidence: 92%
“…Considering that the US has secured 1.1 million of MVA vaccines and that there are an estimated 1.7 million people at high-risk 11 , our results suggest that dose-sparing strategies would outperform full-dose vaccination provided that the fractional-dose retains at least 40% effectiveness of the full-dose. These results are consistent with previous studies for other infectious diseases like cholera 12 13 , influenza 14, 15 and COVID-19 16 , that have found that dose-sparing strategies are optimal when the fractional-dose VE is around half as effective as the full dosage. The fewer the doses of MVA vaccine available, the projected payoff from using dose-sparing strategies increases.…”
Section: Discussionsupporting
confidence: 92%
“…For example, the well-known SEIR model, which considers the incubation period by means of introducing a compartment for exposed individuals, has drawn considerable attention (24). After that, the SEIR model and many of its variants were widely applied in studying the transmission of specific infectious diseases such as SARS (25-27), H1N1 (28)(29)(30), Smallpox (31)(32)(33), Ebola (34, 35), and Cholera (36,37). Currently, the classical SEIR model has also been used to model the recent outbreak of COVID-19 (38)(39)(40).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The significant challenge facing public health authorities is how to allocate scarce vaccines to mitigate the negative effects of a pandemic. This type of problem is referred to as vaccine allocation for epidemic control, and it has recently received widespread attention from the scientific community attention (37,47,(49)(50)(51)(52)(53)(54)(55)(56).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation